The Content of the Poetic Story in Arabic Literature from West Africa during the Twentieth Century - Mohamadou Aboubacar Maıga; Mahmud Kaddum (Darulfunun Ilahiyat)
Africans were interested in all aspects of Arabic literature, especially the art of poetry in its many forms, namely, educational, lyrical, religious, social, and political. Narrative poetry is one of the literary arts that has received attention. Contemporary writers in West Africa when they depict African events, realities, heroes, and heroics, base all this on imagination, drawing the stories’ themes from the African environment. It has been determined that although narrative poetry is the focus of attention of West African literary figures, it has yet to be studied by the academic community. Our study will endeavor to address this gap. From these standpoints, this research seeks, through the implementation of descriptive–analytical methods, to shed light on the most beautiful poems of the poetic story written by West African poets, to understand their contributions to this field and to address the subject matter of these poems, their characteristics, their formal structure, and their artistic values. Texts related to this topic have been selected for illustration and not limitation. It is worth noting that the region’s poets have shown great interest in writing the poetic story and have contributed significantly to it. The Ghanaian poet ʻUmar Karakī (d. 1353¤1934), the poet Jarnū Ibrāhīm Sī (d. 1396¤1976), ʻAbbās Ṣall (d. 1410¤1990) from Senegal, the Malian poet Yaʻqūb Dakūre, the Nigerian Jamīl ʻAbd Allāh, the Gambian Bāmyn Muḥammad Sīrī, and the Guinean Jarnū ʻAlī Boudem among others, who excelled in this art.